Associations between hypertension and cognitive, mood, and behavioral parameters in very old adults: results from the IlSIRENTE study - Helio José Coelho-Junior; Riccardo Calvani; Riccardo Calvani; Matteo Tosato; Andrea Russo; Francesco Landi; Francesco Landi; Anna Picca; Anna Picca; Emanuele Marzetti; Emanuele Marzetti (Frontiers Media S.A., 2024)
IntroductionStudies on the associations between hypertension-related parameters and cognitive function, mood, and behavioral symptoms in older adults have produced mixed findings. A possible explanation for these divergent results is that investigations have not adequately adjusted their analyses according to the use of angiotensin-converting enzyme inhibitors (ACEIs). Therefore, the present study examined the cross-sectional associations between hypertension-related parameters, ACEI use, and cognitive function, mood, and behavioral symptoms in very old adults.MethodsThis study was conducted by analyzing the IlSIRENTE database, a prospective cohort study that collected data on all individuals aged 80 years and older residing in the Sirente geographic area (n = 364). Blood pressure (BP) was assessed after 20 to 40 min of rest, while participants sat in an upright position. Drugs were coded according to the Anatomical Therapeutic and Chemical codes. Cognitive function, mood, and behavioral symptoms were recorded using the Minimum Data Set Home Care instrument. Blood inflammatory markers were measured.ResultsHypertension-related parameters were significantly associated with many cognitive, mood, and behavioral parameters after adjustment for covariates. However, only the inverse association between hypertension and lesser problems with short-term memory remained significant. Participants with hypertension had lower blood concentrations of inflammatory markers in comparison to their normotensive peers.ConclusionFindings from the present study indicate that high BP values are associated with fewer complaints about memory problems in very old adults. Furthermore, a lower concentration of inflammatory markers was found in hypertensive participants. ACEI use might affect this scenario.